Awareness and Adoption of UPI Facilities among Working Class Women in An Academic Institution: A Study with Special Reference to Assam Agricultural University, Jorhat, India - Bijoylaxmi Bhuyan; Mira Kalita; Namburi Meenakshi; Sarmistha Mishra; Ngangbam Vedamoni Channu; Sourav Baruah (Archives of Current Research International, 2025)
The rapid growth of digital payment systems in India has reshaped the financial ecosystem, with the Unified Payments Interface (UPI) playing a key role in enabling fast, secure, and cashless transactions. UPI allows users to transfer money instantly using mobile phones, contributing significantly to financial inclusion, especially in underserved areas. Despite its widespread adoption, gaps remain in awareness and usage, particularly among specific demographic groups. This study examines the awareness, usage patterns, and perceptions of UPI services among working-class women at Assam Agricultural University, Jorhat. A random sample of 50 respondents was surveyed using a structured questionnaire, and the data were analyzed using descriptive statistics, t-tests, and Garret ranking techniques. Although most respondents owned Android smartphones and held savings accounts, only 42 per cent had installed banking apps. Awareness of mobile banking was reported by 56 per cent, and online security concerns were prevalent 49 per cent were aware of internet fraud, while 5 per cent had experienced financial loss due to cybercrime. UPI was mainly used for small transactions like mobile recharges, grocery shopping, and DTH payments, with limited use for higher-value payments such as utility bills or rent. Interestingly, educational level showed no significant impact on UPI adoption. The findings underscore the need for targeted digital literacy initiatives, simplified user interfaces, and stronger cyber security awareness. In conclusion, while UPI has revolutionized its effective use among working-class women requires focused efforts to build trust, enhance accessibility, and promote financial empowerment through inclusive digital practices.